Dinamika Pendidikan di Pondok Pesantren Dalam Pengkaderan Ulama - Muhammad Aman Ma'mun; Suhadi Suhadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
The aim of this study was to describe how the role of Pondok Pesantren in cadre ulama. This research was expected to be able to find out a good Pondok Pesantren for cadre ulama. This study was Library Research where the author used a descriptive normative research approach with more emphasis on the strength of data analysis on existing data sources. The results showed that Pondok Pesantren in the essence were to realize the Indonesian Muslim people who believe and devote to Allah SWT. More specifically, Pondok Pesantren were expected to invent cadre Ulama with Islamic quality, faith and morality. The process of cadre Ulama in Pondok Pesantren has variations, for instance Pondok Pesantren (salaf) has have jargon to preserve kitab kuning and to producee the cadre ulama which has identical religious knowledge (tafaqquh fiddin). Hence Santri understood the problems in religion. Keywords: Cadre Ulama, Dynamic of Cadre Pondok Pesantren